Pengklasifikasian Status Kerja pada Angkatan Kerja di Kabupaten Tanah Datar Menggunakan Metode CART dan Metode CHAID - Yulia Rizki Fajriati; Syafriandi - Syafriandi (UNIVERSITAS NEGERI PADANG, 2022)
Tanah Datar Regency experiencing an increase in population, but the number of workforce doesn’t increase. It makes the number of population with the workforce imbalance so that the public welfare decreased. Beside decreasing in public welfare, the workforce also has impacts in their employment status. Therefore, the classification needs to bee done to find out the dominant factors to identified certain characteristics from certain segment using CART and CHAID methods. The results from CART and CHAID methods has obtained that the marriage status is the most dominant variable in classifying employment status in Tanah Datar Regency. Meanwhile, the best methods to classify the employment status in workforce in Tanah Datar Regency is CART method. It can be seen from the 73,9% accuracy and 26,1% of APER